Effect of Bi substitution on structural, optical, magnetic and electrical properties of Nd₁₋ₓBiₓMnO₃ and Nd₀.₇₅₋ₓBiₓNa₀.₂₅MnO₃ / Nurul Atiqah Azhar - Azhar, Nurul Atiqah (2023)
The samples of Nd1-xBixMnO3 (x = 0, 0.25 and 0.50) and Nd0.75-xBixNa0.25MnO3 (x = 0, 0.05, 0.10 and 0.15) were synthesised using a conventional solid-state method to investigate the effect of Bi substitution on their structural, optical, magnetic, and electrical properties. The XRD analysis using the Rietveld refinement method has shown an increase in structural parameters and unit cell volume as Bi was substituted to both samples, indicating the possibility of substitution for the A-site. The FTIR analysis was carried out for all the samples and showed a significant band around 550 to 600 cm-1, corresponding to the vibration of Mn-O bonds. The SEM and EDX analysis were performed for all the samples, and the average grain size for all the samples was increased as Bi was substituted into the system. The morphologies of the samples also revealed that all the samples were agglomerated and non-spherical in shape. The EDX spectrum shows that all the elements existed in the samples. The UV-Vis measurement for all the samples has been analysed using two different methods: Kubelka-Munk and Tauc’s plot. The value of bandgap obtained for both methods are comparable and decreased as the substitution of Bi in the samples increased from 3.44 eV to 1.85 eV for Nd1-xBixMnO3 (x = 0, 0.25 and 0.50) and from 2.32 eV to 2.24 eV for Nd0.75-xBixNa0.25MnO3 (x = 0, 0.05, 0.10 and 0.15). The magnetic properties of the samples were analysed using AC susceptibility and showed a transition of antiferromagnetic (AFM) to paramagnetic (PM) for all the samples. The samples of Nd1-xBixMnO3 (x = 0, 0.25 and 0.50) show a decrease in Neel temperature, TN and Curie temperature, TC, which indicates the weakening of the ferromagnetic behaviour due to double exchange interaction. On the other hand, the appearance of the charge ordering temperature, TCO, was observed for the Nd0.75-xBixNa0.25MnO3 samples at ~ 176 K (x=0) and disappeared at further substitution. The Neel temperature, TN for the samples at x=0 to x=0.15 were decreased from 188 K to 178 K. The electrical properties for the Nd0.75-xBixNa0.25MnO3 were determined using the resistivity measurement has shown that all the Bi-doped samples exhibit insulating behaviour for the entire temperature region. The insulator region was fitted using small polaron hopping (SPH) model, showing an increase in activation energy from 176 meV to 197.89 meV.